Impact of a Direct Oral Anticoagulant Population Management Tool on Anticoagulation Therapy Monitoring in Clinical Practice. Issue 8 (August 2019) - Valencia, Daniela; Spoutz, Patrick; Stoppi, Jaclyn; Kibert, Jeffery L.; Allen, Arthur; Parra, David; Hough, Augustus
Background: The optimal monitoring and follow-up strategy for long-term direct oral anticoagulant (DOAC) therapy has not been established. Historically, at our medical center, DOAC patients were referred to a clinical pharmacy specialist managed anticoagulation clinic (AC) for monitoring via regularly scheduled encounters (face-to-face or telephone).Objective: To determine if implementation of a DOAC Population Management Tool (PMT) designed to identify patients who most likely require clinical review and possibly intervention, would improve the efficacy (interventions per patient) and efficiency (time invested to generate an intervention) of monitoring over AC practices.Methods: The DOAC PMT group included patients flagged as potentially having a dosing issue or history of valve replacement. The AC group included patients who were scheduled for routine DOAC follow-up. The quantity and character of interventions made were prospectively recorded and compared.Results: A total of 399 patients were included. Data were collected for 131 patients identified by the DOAC PMT, resulting in a review of 170 flags with a total of 94 interventions or 0.55 interventions per flag reviewed. For the AC group, 268 patients were evaluated, leading to 53 interventions or 0.20 interventions per patient encounter ( P < 0.001 for comparison). The time to generate an intervention was 16 minutes in the DOAC PMT versus 64 minutes for the AC group.Conclusion and Relevance: A population-based approach to DOAC monitoring represents a more effective and efficient strategy to reduce missed opportunities for interventions between follow-up appointments while also increasing clinic access, particularly for patients who require immediate attention.